DIVERSITY OF NECROPHAGOUS BLOWFLY (DIPTERA: CALLIPHORIDAE) OF MEDICAL AND VETERINARY IMPORTANCE IN URBAN ENVIRONMENTS IN CÓRDOBA (ARGENTINA) (2016)
The complex nature of urban environments can have different effects on species diversity and composition. The aim of this work was to characterize the assemblage of Calliphoridae regarding its richness, abundance, and synanthropy in Córdoba City, Argentina. Three sampling sites differing in their distance to the border of the city and degree of urbanization were selected. In each site, collections were carried out with 12 traps baited with cow liver (200 g per trap) that were operated for five consecutive days during three different times of the year, in April, June and August 2013. A total of 341 adult calliphorids from nine species, Lucilia sericata (Meigen), L. eximia (Wiedemann), L. cuprina (Wiedemann), L. cluvia (Walker), Calliphora vicina Robineau-Desvoidy, Sarconesia chlorogaster (Wiedemann), Chrysomya albiceps (Wiedemann), C. megacephala (Fabricius) and C. chloropyga (Wiedemann) were collected. Lucilia sericata was the most abundant species followed by C. vicina. Species diversity, composition and abundance changed between sites, richness being lowest at the most urbanized site. All species are cosmopolitan except Sarconesia chlorogaster, whose distribution is restricted to South America. These results are consistent with a homogenization of the fauna in urban environments.